Stan Lee's lucky man. Season one [videorecording (DVD)] - Lee, Stan, 1922-2018 (Universal Pictures Home Entertainment, 2017)
DI Harry Clayton is a detective in central London's murder squad suffering from a gambling addiction. After a night spent with the mysterious Eve, he wakes up with an ancient bracelet on his wrist and discovers that it gives him supernatural luck. With his gambling addiction having cost him his wife and daughter and being in debt for thousands of pounds to a casino owner, Clayton soon begins to use the bracelet to his own advantage.